What Are the Applications of AI in Epilepsy Management? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Artificial intelligence (AI) is no longer a futuristic concept but a present-day reality that is reshaping various sectors, including healthcare. For complex...
Keywords: AI in Neurology; Applications; Epilepsy; Management; Artificial Intelligence; Machine Learning; Deep Learning